1997
DOI: 10.1021/bi970691k
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure and Resonance Raman Studies of Protocatechuate 3,4- Dioxygenase Complexed with 3,4-Dihydroxyphenylacetate,

Abstract: The crystal structure of the anaerobic complex of Pseudomonas putida protocatechuate 3,4-dioxygenase (3,4-PCD) bound with the alternative substrate, 3,4-dihydroxyphenylacetate (HPCA), is reported at 2.4 A resolution and refined to an R factor of 0.17. Formation of the active site Fe(III).HPCA chelated complex causes the endogenous axial tyrosinate, Tyr447 (147beta), to dissociate from the iron and rotate into an alternative orientation analogous to that previously observed in the anaerobic 3,4-PCD.3,4-dihydrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
113
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(117 citation statements)
references
References 35 publications
4
113
0
Order By: Relevance
“…The slowest phase has an RRT very similar to k cat from steady-state experiments (0.18 s −1 at 4°C). In all previous studies, we and others have found that product release is the rate-limiting step for IDOs, and the preceding ringopening step is irreversible (12,24,25,35). This irreversible step allows the slowest RRT to be associated with the rate constant for a specific step in the reaction, presumably product release.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…The slowest phase has an RRT very similar to k cat from steady-state experiments (0.18 s −1 at 4°C). In all previous studies, we and others have found that product release is the rate-limiting step for IDOs, and the preceding ringopening step is irreversible (12,24,25,35). This irreversible step allows the slowest RRT to be associated with the rate constant for a specific step in the reaction, presumably product release.…”
Section: Resultsmentioning
confidence: 76%
“…In 3,4-PCD this coordination mode comes about as a result of the rearrangement described above and is stabilized by interaction with second sphere conserved residues Q477 and R457. As shown in Axial binding of catecholic substrates is a characteristic of all classes of IDOs (20,23,35,42). The alternative equatorial 4FC binding mode provides insights into the driving force behind the substrate binding-mediated dissociation of Y447.…”
Section: Relationship To Spectroscopic and Computational Studies Of Tmentioning
confidence: 99%
“…The refinement of the enzyme-DHB complex is described elsewhere. 2 The procedures were similar, but the substrate-binding site was fully occupied by DHB so that the use of two models of the active site was not necessary.…”
Section: ϫ2mentioning
confidence: 99%
“…Consistent with previous studies (13), the apparent specificity of DHBD in air-saturated buffer is 350-fold higher for DHB than for catechol. Although the K mO 2 of DHBD in the presence of catechol could not be evaluated, at a concentration of 1275 M catechol, the apparent constant, K mO 2 app was 1000 Ϯ 160 M.…”
Section: Stabilization and Inhibition Of An Extradiol Dioxygenasementioning
confidence: 99%
See 1 more Smart Citation